2016
DOI: 10.1002/adfm.201603182
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Random Access Memory and Energy Storage Based on Antiferroelectric Like Hysteresis in ZrO2

Abstract: To date antiferroelectrics have not been considered as nonvolatile memory elements because a removal of the external field causes a depolarization, resulting in a loss of the stored information. In comparison to ferroelectrics, antiferroelectrics are known for their enhanced fatigue resistance. Therefore, the main scope of this study is the development of a new memory device concept that would enable the usage of antiferroelectrics as a nonvolatile material with improved wake‐up and enhanced endurance properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 190 publications
(85 citation statements)
references
References 33 publications
1
84
0
Order By: Relevance
“…The corresponding potential to explain the field-induced phase transition equals that of a first-order phase transition slightly above the Curie temperature with a stable centric minimum (unipolar state, tetragonal phase) and two symmetric, metastable eccentric minima (ferroelectric phase with two spontaneous polarization states). Here, no strong effect of internal bias fields is anticipated (at least in a perfectly symmetric stack [50] ) as no polar grains are present that could promote a certain defect/charge movement/formation. By applying a certain positive or negative field, this potential can be tilted as shown in Figure 6c and one of the polar states becomes the new stable state.…”
Section: Wwwadvelectronicmatdementioning
confidence: 94%
“…The corresponding potential to explain the field-induced phase transition equals that of a first-order phase transition slightly above the Curie temperature with a stable centric minimum (unipolar state, tetragonal phase) and two symmetric, metastable eccentric minima (ferroelectric phase with two spontaneous polarization states). Here, no strong effect of internal bias fields is anticipated (at least in a perfectly symmetric stack [50] ) as no polar grains are present that could promote a certain defect/charge movement/formation. By applying a certain positive or negative field, this potential can be tilted as shown in Figure 6c and one of the polar states becomes the new stable state.…”
Section: Wwwadvelectronicmatdementioning
confidence: 94%
“…For pure HfO 2 , a paraelectric response is typically observed due to the stabilization of the monoclinic phase. For pure ZrO 2 , in contrast, antiferroelectric behavior was reported that is attributed to the tetragonal phase and an electric field–driven phase transition to the orthorhombic phase . For La doping of HfO 2 , Schroeder et al reported a remanent polarization ( P r ) of more than 30 µC cm −2 if doped in with a concentration of about 10 cat%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore this discovery has drastically changed the view on ferroelectric memories [19]. Both the scaling of classical capacitor based memories as well as the realization of FeFET based memories seem to be in reach again [20,21] and even the possibility of making classical DRAM non-volatile has been pointed out recently [22,23]. However, in order to apply the unexpected ferroelectric behavior of hafnium oxide to reliable products a number of fundamental questions need to be answered: the origin of the ferroelectric phase, the control of the influencing process parameters, the device and array concepts as well as the degradation under use conditions.…”
Section: Introductionmentioning
confidence: 99%